Nonaqueous electrolyte storage element and storage device

A non-aqueous electrolyte composition with fluorinated cyclic carbonate and sulfur-based cyclic compounds stabilizes lithium metal electrodes, addressing volume expansion and enhancing discharge capacity in lithium metal-based batteries.

JP7600994B2Active Publication Date: 2024-12-17GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021545149
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-11
Filing Date
2020-07-21
Publication Date
2024-12-17
Estimated Expiration
2040-07-21

AI Technical Summary

Technical Problem

Non-aqueous electrolyte secondary batteries using lithium metal as the negative electrode suffer from significant volume increase due to continuous reductive decomposition of the electrolyte on the lithium metal surface, leading to gas accumulation during charging and discharging.

Method used

A non-aqueous electrolyte formulation containing fluorinated cyclic carbonate and a sulfur-based cyclic compound, with the fluorinated cyclic carbonate exceeding 20% by volume, forms a stable film on the lithium metal surface, suppressing continuous electrolyte decomposition and reducing gas generation.

Benefits of technology

The solution effectively suppresses volume increase and enhances discharge capacity retention by minimizing electrolyte decomposition and dendrite formation, improving the battery's performance over charge/discharge cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600994000005
    Figure 0007600994000005
  • Figure 0007600994000006
    Figure 0007600994000006
  • Figure 0007600994000001
    Figure 0007600994000001
Patent Text Reader

Abstract

In one embodiment, this nonaqueous electrolyte power storage element is provided with a negative electrode, a positive electrode and a nonaqueous electrolyte, wherein the negative electrode has a negative electrode active material layer containing a lithium metal, the nonaqueous electrolyte contains fluorinated cyclic carbonate, a chain carbonate and a sulfur-base cyclic compound, and, in the entire solvent of the nonaqueous electrolyte, the content of the aforementioned fluorinated cyclic carbonate exceeds 20 vol%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and an electricity storage device. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries.

[0003] In recent years, in order to increase the capacity of non-aqueous electrolyte secondary batteries, there has been a demand for high-capacity negative electrodes. Lithium metal has a significantly larger discharge capacity per active material mass than graphite, which is currently widely used as a negative electrode active material for lithium-ion secondary batteries. For this reason, non-aqueous electrolyte secondary batteries using metallic lithium as the negative electrode active material have been proposed (see JP 2011-124154 A). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-124154 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, non-aqueous electrolyte secondary batteries using lithium metal in the negative electrode have the disadvantage of being prone to volume increase, which is presumably due to the fact that the non-aqueous electrolyte is continuously reduced and decomposed on the active lithium metal that is continuously produced as the lithium metal negative electrode dissolves and precipitates during charging and discharging, and gas that is a decomposition product accumulates.

[0006] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a nonaqueous electrolyte electricity storage element and an electricity storage device that can suppress an increase in volume. [Means for solving the problem]

[0007] One aspect of the present invention made to solve the above problems is a nonaqueous electrolyte storage element comprising a negative electrode, a positive electrode, and a nonaqueous electrolyte, wherein the negative electrode has a negative electrode active material layer containing lithium metal, the nonaqueous electrolyte contains a fluorinated cyclic carbonate, a chain carbonate, and a sulfur-based cyclic compound, and the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20 volume %.

[0008] Another aspect of the present invention is an electricity storage device including a plurality of the nonaqueous electrolyte electricity storage elements. Effect of the Invention

[0009] According to the present invention, it is possible to provide a nonaqueous electrolyte electricity storage element and an electricity storage device capable of suppressing an increase in volume. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] A nonaqueous electrolyte storage element according to one embodiment of the present invention is a nonaqueous electrolyte storage element comprising a negative electrode, a positive electrode, and a nonaqueous electrolyte, wherein the negative electrode has a negative electrode active material layer containing lithium metal, the nonaqueous electrolyte contains a fluorinated cyclic carbonate, a chain carbonate, and a sulfur-based cyclic compound, and the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20% by volume.

[0012] According to the nonaqueous electrolyte storage element, the nonaqueous electrolyte contains a fluorinated cyclic carbonate, a chain carbonate, and a sulfur-based cyclic compound, and the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20% by volume, thereby suppressing the increase in the volume of the nonaqueous electrolyte storage element. The reason for this is unclear, but is presumed to be as follows. As described above, the increase in volume of a nonaqueous electrolyte secondary battery using lithium metal in the negative electrode is presumed to be due to the fact that the nonaqueous electrolyte is continuously reduced and decomposed on the active lithium metal that is continuously generated along with the dissolution and deposition of the negative electrode containing lithium metal during charging and discharging, and the decomposition product gas accumulates. That is, in a nonaqueous electrolyte secondary battery using lithium metal, when the nonaqueous electrolyte comes into contact with the lithium metal, the nonaqueous electrolyte is reduced and decomposed, and a coating is formed on the surface of the lithium metal, thereby suppressing the nonaqueous electrolyte from being further continuously reduced and decomposed on the lithium metal. However, when the negative electrode containing lithium metal is dissolved and deposited during charging and discharging, active lithium metal without a coating is continuously generated each time. Therefore, unlike the case of a negative electrode in which a carbon material such as graphite is used as the negative electrode active material, in the case of a nonaqueous electrolyte secondary battery in which lithium metal is used for the negative electrode, the reaction of the nonaqueous electrolyte being reduced and decomposed on the lithium metal occurs continuously, and the generation of gas, which is a decomposition product, is also continuous.

[0013] According to one embodiment of the present invention, the content of the fluorinated cyclic carbonate contained in the non-aqueous electrolyte exceeds 20% by volume relative to the total solvent, so that a coating that is difficult to be reduced and decomposed is quickly formed on the lithium metal, the continuous reduction and decomposition of the non-aqueous electrolyte on the lithium metal is suppressed, and the amount of gas generated as a decomposition product is reduced. Furthermore, the sulfur-based cyclic compound contained as an additive causes the decomposition reaction of the sulfur-based cyclic compound on the lithium metal at an appropriate potential, so that a coating that is difficult to be reduced and decomposed is quickly formed on the lithium metal, and the generation of the gas is suppressed. Therefore, it is considered that the volume increase of the non-aqueous electrolyte storage element can be suppressed by combining the fluorinated cyclic carbonate and the sulfur-based cyclic compound.

[0014] In addition, by making the content of the fluorinated cyclic carbonate more than 20% by volume based on the total solvent, the amount of inactive lithium dendrites that are not involved in the charge-discharge reaction and that accumulate on the lithium metal with repeated charge-discharge cycles is effectively reduced, thereby preventing the negative electrode containing lithium metal from becoming inactive. Therefore, in addition to the effect of preventing the volume increase of the nonaqueous electrolyte storage element, the discharge capacity retention rate with charge-discharge cycles can also be increased.

[0015] The fluorinated cyclic carbonate is preferably fluoroethylene carbonate. The fluoroethylene carbonate has high oxidation resistance and can suppress side reactions (oxidative decomposition of nonaqueous solvents, etc.) that may occur during charging and discharging of the nonaqueous electrolyte storage element. In addition, fluoroethylene carbonate is reductively decomposed at a relatively noble potential to rapidly form a stable coating on lithium metal, thereby suppressing continuous reductive decomposition of the nonaqueous electrolyte on the lithium metal. Therefore, when the fluorinated cyclic carbonate is fluoroethylene carbonate, the effect of suppressing the volume increase of the nonaqueous electrolyte storage element can be further improved.

[0016] The non-aqueous electrolyte preferably has a sulfur-based cyclic compound having a sultone structure or a cyclic sulfate structure. The sulfur-based cyclic compound has the above structure, so that the decomposition reaction of the sulfur-based cyclic compound occurs at a potential higher than the potential at which a fluorinated cyclic carbonate such as fluoroethylene carbonate decomposes, and the decomposition product produced by this reaction forms a more stable coating on the lithium metal surface. Therefore, the sulfur-based cyclic compound having a sultone structure or a cyclic sulfate structure can further enhance the effect of suppressing the volume increase of the non-aqueous electrolyte storage element.

[0017] Hereinafter, a nonaqueous electrolyte electricity storage element according to an embodiment of the present invention will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0018] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element according to an embodiment of the present invention includes a negative electrode, a positive electrode, and a nonaqueous electrolyte. Hereinafter, a nonaqueous electrolyte secondary battery will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a case, and the case is filled with a nonaqueous electrolyte. In the nonaqueous electrolyte secondary battery, the above-mentioned nonaqueous electrolyte is used as the nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the case, a known metal case, a resin case, or the like that is usually used as a case for a nonaqueous electrolyte secondary battery can be used.

[0019] [Negative electrode] The negative electrode includes a negative electrode substrate and a negative electrode active material layer laminated directly or indirectly on at least one surface of the negative electrode substrate. The negative electrode may include an intermediate layer disposed between the negative electrode substrate and the negative electrode active material layer.

[0020] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil. The term "electrically conductive" refers to a material having a volume resistivity of 1×10 as measured in accordance with JIS-H0505 (1975). 7 "Non-conductive" means that the volume resistivity is 1×10 7 This means that the resistance is greater than Ω·cm.

[0021] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased while increasing the energy density per volume of the nonaqueous electrolyte secondary battery. The "average thickness of the substrate" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate.

[0022] (Negative electrode active material layer) The negative electrode active material layer contains lithium metal as a negative electrode active material. When the negative electrode active material contains lithium metal, the discharge capacity per active material mass can be improved. The lithium metal includes lithium simple substance as well as lithium alloys. Examples of the lithium alloy include lithium aluminum alloys. The negative electrode containing lithium metal can be manufactured by cutting or forming lithium metal into a predetermined shape.

[0023] Furthermore, the negative electrode active material layer may contain elements such as Na, K, Ca, Fe, Mg, Si, and N.

[0024] The lower limit of the lithium metal content in the negative electrode active material is preferably 80 mass %, more preferably 90 mass %, and even more preferably 95 mass %, while the upper limit of this content may be 100 mass %.

[0025] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer is laminated directly or via an intermediate layer along at least one surface of the positive electrode substrate.

[0026] The positive electrode substrate has electrical conductivity. As the material of the substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc., or alloys thereof are used. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high electrical conductivity, and cost. In addition, the form of the positive electrode substrate may be foil, vapor deposition film, etc., and foil is preferred in terms of cost. That is, aluminum foil is preferred as the positive electrode substrate. In addition, examples of aluminum or aluminum alloys include A1085, A3003, etc., as specified in JIS-H4000 (2014).

[0027] The positive electrode active material layer is formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer further contains optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0028] The positive electrode active material can be appropriately selected from, for example, known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as a positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γCo (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β≦1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. However, the positive electrode active material is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 When using a lithium transition metal composite oxide represented by LiO2, the effect of suppressing the volume increase may be lower than that of other positive electrode active materials. x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be mixed and used. In the positive electrode active material layer, one of these compounds may be used alone, or two or more of them may be mixed and used. The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but the lower limit is preferably 50 mass%, more preferably 80 mass%, and even more preferably 90 mass%. On the other hand, the upper limit of this content is preferably 99% by mass, more preferably 98% by mass.

[0029] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0030] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0031] Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. The content of the binder in the positive electrode active material layer is preferably 1% by mass or more and 10% by mass or less, more preferably 3% by mass or more and 9% by mass or less.

[0032] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like.

[0033] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0034] The intermediate layer is a coating layer on the surface of the positive electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. As with the negative electrode, the configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.

[0035] [Non-aqueous electrolyte] The non-aqueous electrolyte contains a non-aqueous solvent, and a sulfur-based cyclic compound and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent includes a fluorinated cyclic carbonate and a chain carbonate. The non-aqueous electrolyte is not limited to a liquid. That is, the non-aqueous electrolyte is not limited to a liquid, but also includes a solid or gel electrolyte.

[0036] (Non-aqueous solvent) The non-aqueous solvent includes a fluorinated cyclic carbonate and a chain carbonate.

[0037] The non-aqueous solvent can reduce the viscosity of the non-aqueous electrolyte by using a chain carbonate, such as diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diphenyl carbonate, trifluoroethyl methyl carbonate (TFEMC), and bis(trifluoroethyl) carbonate.

[0038] The lower limit of the content of the chain carbonate in the non-aqueous solvent is preferably 30% by volume, more preferably 40% by volume, and even more preferably 50% by volume. Meanwhile, the upper limit is preferably 80% by volume, and more preferably 70% by volume. By setting the content of the chain carbonate in the above range, the charge-discharge cycle performance of the non-aqueous electrolyte storage element can be further improved.

[0039] The content of the fluorinated cyclic carbonate in the total solvent of the non-aqueous electrolyte exceeds 20% by volume. On the other hand, the upper limit of the content of the fluorinated cyclic carbonate is preferably 70% by volume, more preferably 50% by volume. When the content of the fluorinated cyclic carbonate contained in the non-aqueous electrolyte is within the above range, the non-aqueous electrolyte is prevented from being continuously reduced and decomposed on the lithium metal, and the amount of gas generated as a decomposition product is reduced. In addition, the amount of inactive lithium dendrites that are not involved in the charge and discharge reaction and that accumulate on the lithium metal is effectively reduced, and the discharge capacity retention rate associated with the charge and discharge cycles can also be increased.

[0040] Examples of the fluorinated cyclic carbonate include fluorinated ethylene carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate, fluorinated propylene carbonate, and fluorinated butylene carbonate. Among these, fluorinated ethylene carbonate is preferred, and fluoroethylene carbonate is more preferred. The fluoroethylene carbonate has high oxidation resistance and is highly effective in suppressing side reactions (oxidative decomposition of nonaqueous solvents, etc.) that may occur during charging and discharging of a nonaqueous electrolyte storage element. In addition, fluoroethylene carbonate is reductively decomposed at a relatively noble potential to rapidly form a stable coating on lithium metal, so that continuous reductive decomposition of nonaqueous electrolyte on lithium metal can be suppressed. Therefore, when the fluorinated cyclic carbonate is fluoroethylene carbonate, the effect of suppressing the volume increase of the nonaqueous electrolyte storage element can be further improved. The fluorinated cyclic carbonates can be used alone or in combination of two or more.

[0041] The non-aqueous solvent may contain an organic solvent other than the fluorinated cyclic carbonate and the chain carbonate. Examples of the other organic solvent include cyclic carbonates other than the fluorinated cyclic carbonate, esters, ethers, amides, lactones, nitriles, etc. In addition to the sulfur-based cyclic compound contained as an additive, the non-aqueous solvent may contain an organic solvent containing sulfur, such as sulfones and sulfites.

[0042] Examples of cyclic carbonates other than the fluorinated cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Examples of the esters include methyl 3,3,3-trifluoropropionate (FMP). Examples of the sulfones include sulfolane (SL), ethyl isopropyl sulfone (EiPSO2), and ethyl methyl sulfone (EMSO2). Examples of the sulfites include diethyl sulfite (DES), dimethyl sulfite (DMS), and the like.

[0043] (Sulfur-based cyclic compounds) The nonaqueous electrolyte of the nonaqueous electrolyte storage element contains a sulfur-based cyclic compound as an additive. By containing the sulfur-based cyclic compound as an additive, the decomposition reaction of the sulfur-based cyclic compound occurs at an appropriate potential on lithium metal. Therefore, the amount of gas generated as a decomposition product of the nonaqueous electrolyte is reduced, and the volume increase of the nonaqueous electrolyte storage element can be suppressed.

[0044] Examples of the sulfur-based cyclic compound include compounds having a sultone structure, compounds having a cyclic sulfate structure, sulfones, sulfites, and the like. Among these, compounds having a sultone structure or a cyclic sulfate structure are preferred. By the sulfur-based cyclic compound having the above structure, a decomposition reaction occurs at an appropriate potential, and the decomposition product generated by this reaction effectively forms a coating on the lithium metal surface. Therefore, the effect of suppressing the volume increase of the nonaqueous electrolyte storage element can be further improved. The sulfur-based cyclic compound can be used alone or in combination of two or more.

[0045] Examples of the compound having the sultone structure include 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, and 1,4-butene sultone.

[0046] Examples of the compound having a cyclic sulfate structure include ethylene sulfate, 1,3-propylene sulfate, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), and sulfate ester compounds represented by the following formula (1).

[0047] [ka]

[0048] In formula (1), R 1 and R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.

[0049] Examples of the hydrocarbon group having 1 to 3 carbon atoms include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, or an i-propyl group, and alkenyl groups such as a vinyl group.

[0050] Above R 1 is preferably a hydrogen atom.

[0051] Above R 2 As the alkyl group, a hydrocarbon group having 1 to 3 carbon atoms is preferable, an alkyl group having 1 to 3 carbon atoms is more preferable, and a methyl group is further preferable.

[0052] The lower limit of the content of the sulfur-based cyclic compound in the non-aqueous electrolyte is preferably 0.1% by mass, more preferably 0.3% by mass, and even more preferably 0.5% by mass. Meanwhile, the upper limit of this content is preferably 10% by mass, more preferably 5% by mass. By making the content of the sulfur-based cyclic compound equal to or greater than the lower limit and equal to or less than the upper limit, the effect of suppressing the increase in volume of the non-aqueous electrolyte storage element can be further improved. Note that, when the content of the sulfur-based cyclic compound is less than 10% by mass, the sulfur-based cyclic compound is contained in the non-aqueous electrolyte as the additive, and when the content is equal to or greater than 10% by mass, the sulfur-based cyclic compound is contained in the non-aqueous electrolyte as the non-aqueous solvent.

[0053] (Electrolyte salt) The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte storage element, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.

[0054] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a fluorohydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0055] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte is 0.1 mol dm -3 is preferred, and 0.3 mol dm -3 is more preferred, and 0.5 mol dm -3 On the other hand, the upper limit is not particularly limited, but is preferably 3 mol dm -3 is preferred, and 2 mol dm -3 is more preferred.

[0056] (Other additives, etc.) The non-aqueous electrolyte may contain other additives other than the sulfur-based cyclic compound and the electrolyte salt, as long as they do not impair the effects of the present invention. Examples of the other additives include various additives contained in general non-aqueous electrolyte storage elements. The total content of the other additives in the non-aqueous electrolyte is preferably 10% by mass or less, and more preferably 5% by mass or less.

[0057] The non-aqueous electrolyte can usually be obtained by adding and dissolving each of the components, such as the sulfur-based cyclic compound and the electrolyte salt, in the non-aqueous solvent.

[0058] [Separator] As the separator, for example, a woven fabric, a nonwoven fabric, a porous resin film, etc. are used. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of nonaqueous electrolyte retention. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferable from the viewpoint of strength, and a polyimide or aramid is preferable from the viewpoint of oxidation decomposition resistance. These resins may also be combined.

[0059] An inorganic layer may be disposed between the separator and the electrode (usually, the positive electrode). This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one side of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components.

[0060] [Specific configuration of the energy storage element] FIG. 1 is a schematic diagram of a rectangular nonaqueous electrolyte storage element 1 (nonaqueous electrolyte secondary battery) which is one embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure is a see-through view of the inside of a case 3. In the nonaqueous electrolyte storage element 1 shown in FIG. 1, an electrode body 2 is housed in a case 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode current collector 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode current collector 5'. A nonaqueous electrolyte is injected into the case 3.

[0061] The shape of the nonaqueous electrolyte storage element according to the present invention is not particularly limited, and examples include a cylindrical battery, a prismatic battery (a rectangular battery), and a flat battery.

[0062] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for manufacturing the nonaqueous electrolyte storage element according to the present embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, a step of preparing an electrode body, a step of preparing a nonaqueous electrolyte, and a step of housing the electrode body and the nonaqueous electrolyte in a case. The step of preparing the electrode body includes a step of preparing a positive electrode and a negative electrode, and a step of forming the electrode body by stacking or winding the positive electrode and the negative electrode with a separator interposed therebetween.

[0063] The process of housing the non-aqueous electrolyte in the case can be appropriately selected from known methods. For example, when using a liquid non-aqueous electrolyte (also called "electrolyte"), the electrolyte is injected from an injection port formed in the case, and then the injection port is sealed. Details of the other elements constituting the storage element obtained by this manufacturing method are as described above.

[0064] [Other embodiments] The nonaqueous electrolyte storage element according to the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0065] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but other storage elements may be used. Examples of other storage elements include capacitors (electric double layer capacitors, lithium ion capacitors), etc. Examples of nonaqueous electrolyte secondary batteries include lithium ion nonaqueous electrolyte secondary batteries.

[0066] An electricity storage device according to one embodiment of the present invention includes a plurality of nonaqueous electrolyte electricity storage elements according to the above embodiment (hereinafter referred to as "second embodiment"). A single or a plurality of nonaqueous electrolyte electricity storage elements (cells) according to the above embodiment can be used to configure a battery pack, and this battery pack can be used to configure an electricity storage device according to the second embodiment. The electricity storage device according to the second embodiment can be used as a power source for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs). Furthermore, the electricity storage device can be used in various power supply devices such as engine starting power supply devices, auxiliary power supply devices, and uninterruptible power supplies (UPS).

[0067] 2 shows an example of an electricity storage device 30 according to a second embodiment in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, and a bus bar (not shown) that electrically connects two or more electricity storage units 20. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0068] (Volume measurement of non-aqueous electrolyte storage element) In this specification, the volume of a nonaqueous electrolyte storage element is measured by the following method. The mass W1 of a beaker containing 500 ml of ion-exchanged water at 25°C is recorded. Next, the nonaqueous electrolyte storage element to be measured is immersed in the ion-exchanged water in a suspended state. At this time, the position of the nonaqueous electrolyte storage element is adjusted so that the entire nonaqueous electrolyte storage element is immersed and the nonaqueous electrolyte storage element does not contact the bottom or sides of the beaker. The mass W2 at this time is recorded. The volume of the nonaqueous electrolyte storage element is calculated by dividing the difference in mass (W2-W1) by the density of water at 25°C. EXAMPLES

[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0070] The additives used in the examples and comparative examples are shown below. (1) 1,3-Propene sultone (2) 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane) (3) A sulfate ester compound (A) represented by the following formula (A):

[0071] [ka]

[0072] (4) Lithium difluorooxalatoborate (LiDFOB) (5) Vinylene carbonate (6) Lithium difluorophosphate (LiDFP)

[0073] [Example 1] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of FEC:EMC = 30:70, and 1 mol dm LiPF6 was added.-3 A solution was prepared by dissolving the above-mentioned compound at a concentration of 1,3-propene sultone at 2 mass % to prepare a non-aqueous electrolyte.

[0074] (Preparation of positive electrode) The positive electrode active material has an α-NaFeO2 type crystal structure and Li 1+α Me 1-α A lithium transition metal composite oxide represented by O2 (Me is a transition metal) was used. Here, the molar ratio of Li to Me, Li / Me, was 1.33, and Me was composed of Ni and Mn, and was contained in a molar ratio of Ni:Mn=1:2.

[0075] A positive electrode paste was prepared using N-methylpyrrolidone (NMP) as a dispersion medium, containing the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVdF) as a binder in a mass ratio of 94:4.5:1.5. The positive electrode paste was applied to one side of a 15 μm thick aluminum foil as a positive electrode substrate, dried, pressed, and cut to prepare a positive electrode in which a positive electrode active material layer was arranged in a rectangular shape of 30 mm width and 40 mm length. The positive electrode active material layer had a thickness of approximately 100 μm, and the positive electrode mixture was 14 mg / cm per unit area. 2 The positive electrode was dried under reduced pressure at 120° C. for 14 hours or more before use.

[0076] (Preparation of negative electrode) A lithium metal plate with a width of 30 mm, a length of 42 mm, and a thickness of 600 μm was used as the negative electrode plate. The lithium metal plate was pressed at a pressure of 1.4 MPa through a metal-resin composite film, and had a metallic luster. In addition, a stainless steel negative electrode substrate was connected to only the end of the lithium metal plate with a length of 5 mm.

[0077] (Fabrication of non-aqueous electrolyte storage element) A 27 μm thick polypropylene microporous membrane surface-modified with polyacrylate was used as the separator. Four of the separators were stacked and fused around the periphery except for one side to produce a pouch-shaped separator with three pouches. The negative electrode was inserted into the central pouch of the pouch-shaped separator, and two positive electrodes were inserted into the pouches on both sides so that the surfaces on which the positive electrode active material layers were arranged faced the negative electrodes. In this way, a stacked electrode group with two opposing surfaces of positive and negative electrodes was produced.

[0078] The electrode group was housed in a metal resin composite film case so that the open ends of the lead terminals previously connected to the positive and negative electrodes were exposed to the outside, and the case was sealed except for a portion that would become a liquid injection hole. After the nonaqueous electrolyte was injected, the liquid injection hole was hermetically sealed. In this manner, a nonaqueous electrolyte storage element was produced. Here, the capacity per unit area of ​​the negative electrode is about 15 times the capacity per unit area of ​​the opposing positive electrode.

[0079] [Examples 2 to 9 and Comparative Examples 1 to 8] Nonaqueous electrolyte storage elements of Examples 2 to 9 and Comparative Examples 1 to 8 were obtained in the same manner as in Example 1, except that the types and amounts of the solvents and additives used were as shown in Table 1. In the tables below, "-" indicates that the corresponding additive was not used.

[0080] [Reference Examples 1 to 3] Graphite was used as the negative electrode active material. A negative electrode paste was prepared by mixing graphite, styrene butadiene rubber, and carboxymethyl cellulose in a mass ratio of 96.7:2.1:1.2 (solid content equivalent) and using water as a dispersion medium. The negative electrode paste was dispersed in a 10 mg / cm2 negative electrode mixture per unit area. 2The negative electrode active material layer was formed by pressing the negative electrode active material layer with a roller press, and then dried under reduced pressure at 80° C. for 14 hours to remove moisture from the negative electrode. The negative electrode thus obtained was used, and nonaqueous electrolyte storage elements of Reference Examples 1 to 3 were obtained in the same manner as in Example 1, except that the types and amounts of the solvent and additives used were as shown in Table 1. For each of the obtained nonaqueous electrolyte storage elements, the volume before the first charge / discharge was measured using the method described above.

[0081] (First charge / discharge) The obtained nonaqueous electrolyte storage elements were initially charged and discharged under the following conditions: They were charged at a constant current of 0.1 C to 4.60 V at 25° C., and then charged at a constant voltage of 4.60 V. The charge was terminated when the charge current reached 0.05 C. After a 10-minute pause after charging, they were discharged at a constant current of 0.1 C to 2.00 V at 25° C.

[0082] (Initial capacity confirmation test) After the first charge and discharge, an initial capacity confirmation test was conducted under the following conditions. The battery was charged at a constant current of 0.1C at 25°C up to 4.60V, and then charged at a constant voltage of 4.60V. The charge was terminated when the charge current reached 0.05C. After a 10-minute pause after charging, the battery was discharged at a constant current of 1.0C up to 2.00V at 25°C. The discharge capacity obtained in this test was designated the "initial discharge capacity."

[0083] In addition, for the negative electrodes using graphite as the negative electrode active material in Reference Examples 1 to 3, the initial charge / discharge and initial capacity confirmation tests were performed in the same manner as described above, except that the negative electrodes were charged at a constant current of 0.1 C to 4.50 V at 25° C., and then charged at a constant voltage of 4.50 V.

[0084] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. At 25°C, constant current and constant voltage charging was performed with a charging current of 0.33C and a charge cut-off voltage of 4.60V. The charge was terminated until the charging current reached 0.05C. After that, a rest period of 10 minutes was provided. After that, constant current discharging was performed with a discharge current of 0.33C and a discharge cut-off voltage of 2.00V, followed by a rest period of 10 minutes. This charge-discharge cycle was performed 50 times.

[0085] In addition, for the nonaqueous electrolyte storage elements of Reference Examples 1 to 3 using graphite as the negative electrode active material, the charge cut-off voltage in the above initial capacity confirmation test and charge / discharge cycle test was 4.50V.

[0086] Thereafter, a discharge capacity confirmation test after the charge-discharge cycle test was performed in the same manner as the initial capacity confirmation test. The discharge capacity obtained in this test was defined as the discharge capacity after the charge-discharge cycle. The percentage of the discharge capacity after the charge-discharge cycle test to the initial discharge capacity was defined as the "capacity maintenance rate after 50 cycles". In addition, the volume of each nonaqueous electrolyte storage element after the capacity confirmation test in the discharged state was measured using the above method, and the difference from the volume before the initial charge-discharge was calculated to define the volume increase. The initial discharge capacity, the discharge capacity retention rate after 50 cycles, and the volume increase are shown in Table 1.

[0087] [Table 1]

[0088] As shown in Table 1 above, the nonaqueous electrolyte storage elements of Examples 1 to 9, which use a nonaqueous electrolyte in which the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20 volume % and which contains a sulfur-based cyclic compound as an additive, were confirmed to have a high effect of suppressing volume increase.

[0089] In contrast, the nonaqueous electrolyte storage elements according to Comparative Examples 1 to 8, which used nonaqueous electrolytes in which the content of the fluorinated cyclic carbonate was 20% by volume or less or which did not contain a sulfur-based cyclic compound, were inferior in the effect of suppressing volume increase. This shows that only by combining the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeding 20% ​​by volume and the inclusion of a sulfur-based cyclic compound as an additive can the effect of suppressing volume increase during charge-discharge cycles be improved in a nonaqueous electrolyte storage element having a negative electrode having a negative electrode active material layer containing lithium metal.

[0090] Next, when comparing Example 1 with Comparative Example 1, Comparative Example 2, Comparative Example 5, and Comparative Example 6 in terms of the discharge capacity retention rate after 50 cycles, it is found that the discharge capacity retention rate after 50 cycles is improved when the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20 volume %.

[0091] On the other hand, in Reference Examples 1 to 3 in which graphite was used as the negative electrode active material, as can be seen by comparing Reference Examples 2 and 3, the effect of suppressing volume increase by combining a content of the above-mentioned fluorinated cyclic carbonate in the total solvent of the non-aqueous electrolyte of more than 20 volume % with the inclusion of a sulfur-based cyclic compound as an additive was small,

[0092] Furthermore, in comparison between Reference Example 3 and Example 1, in which the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20% by volume and a nonaqueous electrolyte containing a sulfur-based cyclic compound as an additive is used, and Reference Example 1 and Comparative Example 4, in which vinylene carbonate and LiDFP, which are known to be easily decomposed at a base potential, are used as additives, Comparative Example 4, in which lithium metal is used as the negative electrode active material, did not obtain a volume increase suppression effect compared to Example 1, whereas Reference Example 1, in which graphite is used as the negative electrode active material, obtained a high volume increase suppression effect compared to Reference Example 3. This suggests that the mechanism of action of the volume increase suppression effect during charge and discharge cycles is significantly different between a nonaqueous electrolyte storage element having a negative electrode having a negative electrode active material layer containing graphite as the negative electrode active material and a nonaqueous electrolyte storage element having a negative electrode having a negative electrode active material layer containing lithium metal. This is thought to be related to the fact that in a nonaqueous electrolyte storage element including a negative electrode having a negative electrode active material layer containing graphite as the negative electrode active material, a coating derived from vinylene carbonate or LiDFP formed on the graphite during the initial charge continues to exist stably even during charge-discharge cycles, suppressing continuous gas generation due to electrochemical reductive decomposition of the nonaqueous electrolyte, thereby suppressing an increase in the volume of the nonaqueous electrolyte storage element, whereas in a nonaqueous electrolyte storage element including a negative electrode having a negative electrode active material layer containing lithium metal as the negative electrode active material, the formation of a coating derived from vinylene carbonate or LiDFP on the active lithium metal generated during the charge-discharge cycles is slow, causing continuous gas generation due to reductive decomposition of the nonaqueous electrolyte on the lithium metal, which is thought to be the main cause of the volume increase.

[0093] The above results show that the nonaqueous electrolyte storage element has an excellent effect of suppressing volume increase during charge-discharge cycles of a nonaqueous electrolyte storage element having a negative electrode having a negative electrode active material layer containing lithium metal, and that this effect is based on a unique action mechanism that selectively exerts an effect on a negative electrode containing lithium metal as the negative electrode active material. [Industrial Applicability]

[0094] The present invention can be applied to nonaqueous electrolyte electricity storage elements and electricity storage devices used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0095] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 Cases 4 Positive terminal 4' Positive lead 5 Negative terminal 5' Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A negative electrode, a positive electrode, and a non-aqueous electrolyte, the negative electrode has a negative electrode active material layer containing lithium metal, the non-aqueous electrolyte contains a fluorinated cyclic carbonate, a chain carbonate, and a sulfur-based cyclic compound, the content of the fluorinated cyclic carbonate in the total solvent of the nonaqueous electrolyte exceeds 20% by volume; The sulfur-based cyclic compound includes a compound having a sultone structure and a compound having a cyclic sulfate structure represented by the following formula (1): (However, this does not include the non-aqueous electrolyte containing a cyclic imide salt and a cyclic carbonate derivative having a halogen atom.) 【Chemistry 1】 (In the above formula (1), R 1 and R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.)

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the fluorinated cyclic carbonate is fluoroethylene carbonate.

3. 3. An electricity storage device comprising a plurality of the nonaqueous electrolyte electricity storage elements according to claim 1 or 2.

Citation Information

Patent Citations

  • Electrolyte and battery

    JP2006318888A

  • Electrolyte, battery using it, and method for manufacturing electrolyte

    JP2008016424A

  • Electrolytic solution and battery

    JP2008147119A

  • Active material for nonaqueous electrolyte battery, and nonaqueous electrolyte battery

    JP2011124154A

  • Nonaqueous electrolyte power storage element and manufacturing method thereof

    JP2018181772A